Katniss Everdeen's Linguistic Features in Suzanne Collins' The Hunger Games (NOBEL: Journal of Literature and Language Teaching, 2017)
Linguistic features become the main issue analyzed in this study since it gets much attention from numerous academics. To focus the analysis, Lakoff's theory of Women's Linguistic Features is adopted. In addition, Holmes (1992), Sandriani (2012) and Wright (2002)'s features of male's language are also utilized. In the matter of collecting and analyzing the data, the researcher selects qualitative content analysis and descriptive research designs to deeply investigate Katniss' utterances and the author's description. The researcher herself becomes the only instrument as human instrument. Reading and selecting the data from the entire text of The Hunger Games is a part of data collection steps. Then, the procedures of data analysis contain identifying, classifying and elaborating the data. Drawing the conclusion is also the last step required. 23 utterances of women's linguistic features and 45 utterances of men's linguistic features eventually become the result of this study. To conclude, Katniss is linguistically portrayed as following men's linguistic features more frequently than women's linguistic features.